Correlation of blood pressure levels at different time periods throughout the day with total CSVD burden and MRI imaging markers - Yang, Hua; Fan, Xueyi; Shen, Xiangyi; Liang, Li; Hu, Dongyang; Zhang, Yimo; Liu, Li; Qian, Hairong (Frontiers in Neurology, 2023)
Purpose: Hypertension is an important risk factor for atherosclerotic cerebral small vessel disease (CSVD). Higher blood pressure is associated with a higher CSVD burden and more presence of relevant magnetic resonance imaging (MRI) markers. However, the effect of blood pressure level on CSVD burden and imaging markers including white matter hyperintensity (WHM), lacune, enlarged perivascular spaces (EPVS), and cerebral microbleed (CMB) remains unknown. The purpose of this study was to investigate the correlation between blood pressure level and CSVD burden at different time periods throughout the day. Methods: 144 in-patients with CSVD (66.4 ± 9.8 years, 50% male) were enrolled to have brain MRI and 24-h ambulatory blood pressure assessed. Patients were categorized into five groups according to their MRI-evaluated total CSVD burden scores (0 to 4). Spearman correlation analysis was performed to examine the correlation between blood pressure levels at different time periods and the total CSVD score or the markers of periventricular WHM, deep WMH, lacune, EPVS and CMB. Results: Of the 144 patients, 83.3% (120/144) harbored one or more CSVD markers of interest. The systolic blood pressure (SBP) of 24-h, daytime, night-time, and morning differed significantly among the five groups. SBP levels increased significantly with total CSVD score during 24-h (P = 0.018), daytime (P = 0.018) and nighttime (P = 0.035). The Spearman correlation analysis demonstrated that the SBP of 24-h, daytime, night-time, morning, and the diastolic blood pressure (DBP) of 24-h and morning positively and significantly correlated with the total CSVD score (P<0.05). Logistic regression analysis indicated that both morning SBP and DBP were independent risk factors for total CSVD burden (OR=1.13, 95%CI: 1.02 1.23, P=0.015; OR=1.19, 95%CI: 1.06 1.33, P=0.005). The Spearman correlation analysis indicated a significant positive correlation between morning SBP and higher deep WMH Fazekas score (r=0.296, P<0.001), EPVS grade in the basal ganglia (r=0.247, P=0.003), and the presence of lacune and CMB. Morning DBP only correlated positively with the presence of CMB. Conclusion: Higher SBP significantly correlated with total CSVD burden in patients with atherosclerotic CSVD. Early morning blood pressure level is an important indicator to reflect the severity of CSVD patients.